Peningkatan Kapasitas Kader Posyandu dalam Edukasi Nutrisi dan Pemberian Makan pada Balita di RW IV Kupang Krajan Surabaya - Marcellina Rasemi Widayanti; Ni Luh Agustini Purnama; Agung Kurniawan Saputra (Universitas Baiturrahim, 2026)
Posyandu cadres play a strategic role in improving the nutritional status of young children through nutrition education and appropriate feeding practices. However, the cadres’ limited knowledge and skills remain a barrier to the dissemination of nutritional information to the community. This community service activity aims to enhance the capacity of Posyandu cadres in nutrition education and infant feeding in RW IV Kupang Krajan, Surabaya. The methods used included a pre-test, education through interactive lectures, discussions, simulations (role-play), and a post-test to evaluate knowledge improvement. A total of 20 Posyandu cadres participated in this activity. The pre-test results showed that 60% of cadres had good knowledge, 35% had adequate knowledge, and 5% had insufficient knowledge. Following the intervention, the post-test results showed an increase in knowledge, with 95% of cadres demonstrating good knowledge, 5% adequate knowledge, and no cadres in the insufficient knowledge category. Furthermore, the results of observations using a skills assessment sheet showed that 85% of the cadres were able to provide nutrition education and feed infants and young children at a ‘good’ level. This activity was effective in improving the knowledge and skills of Posyandu cadres in nutrition education and feeding infants and young children. It is hoped that this capacity building will support better feeding practices for infants and young children and contribute to the prevention of nutritional problems in the community.